Development of Thermal Models and Analysis of UO2-BeO Fuel during a Loss of Coolant Accident. (26th August 2014) - Chandramouli, Deepthi; Revankar, Shripad T.
Abstract : Small fraction of high conductivity BeO in UO2 fuel significantly improves thermal conductivity and also affects the overall performance of the fuel during steady state operation and during transients. In this study, performance of UO2 -BeO composite under transient conditions such as loss of coolant accident (LOCA), using FRAPTRAN (fuel rod analysis program transient), was carried out. The subroutines in FRAPTRAN code that calculate key thermophysical properties such as thermal conductivity, specific heat capacity, and specific enthalpy were modified to account for the presence of the BeO in UO2 . The fuel performance parameters like gas gap pressure, energy stored in fuel, and temperature profiles were studied. The simulation results showed reductions in fuel centerline temperatures and lower temperature drop across fuel rod cross-section under normal fuel operations. It was observed that there was reduction in gas gap pressure and energy stored in fuel. Transient conditions involving cladding rupture were investigated and important performance parameters such as cladding strain were studied. During these transients, the addition of BeO to UO2 fuel seems beneficiary.